د لرليد او ماموریت ټاکنه - Mangal, Farooq Jan (Farah Research and Scientific Journal, 2025)
Vision and Mission are two strategic concepts that are established, selected, and formulated for various governmental and private institutions, organizations, and projects in order to determine a clear direction, ensure effective leadership, and achieve strategic goals and long-term outcomes. In general, defining and articulating vision and mission is not merely a theoretical exercise, but rather a crucial strategic process that must be documented by organizations, institutions, and projects in light of internal and external realities, values, needs, and available resources. Furthermore, the relevant institution must continuously monitor its implementation step by step and provide the necessary facilities in accordance with its content. Therefore, it can be clearly stated that vision and mission form the vital foundation for unity, motivation, encouragement, and sustainable growth within an organization, enabling each institution to successfully achieve its intended objectives.